Experimental investigation of Brackish Water Desalination using a Semi Spherical Solar Still - Ali A. F. Al-Hamadani; Mohammed G. Al-Azawyb; Mohammed Hameed Ghareeb Al Dulfi (Wasit Journal of Engineering Sciences)
The intensity of radiation reaches 930 W/m2 during April, 2016 in Kut city. Thus this city is suitable to use application of solar energy such as solar still. An experimental study was performed to evaluate the production of Semi Spherical Solar Still (SS-SS) with and without Charcoal. It was measured in the climatic conditions of Kut, Wasit (32o N latitude), Iraq. The still consists of square basin of length 0.3 m and area 0.09 m2 made of Aluminum. The square absorber basin is painted with black paint for maximum absorption of incident solar radiation. It was found that the productivity of Semi spherical solar still without charcoal is better than the using of charcoal at depth of basin water (dbw=1.5 & 2cm). The productivity of SS-SS without charcoal was 2.7 lit/m2 for 6 hours at total irradiation 5935 W/m2. Whereas 2.5 lit/m2 for SS-SS with charcoal at total irradiation 5845 W/m2 for dbw=1.5cm. In addition, the instantaneous efficiency reaches 58% without charcoal and 70% with charcoal at dbw=1.5cm at 3:00PM. The salinity of water before desalination in SS-SS was 999.54 ppm and becomes 4.06 ppm after desalination. It could be concluded that the semi spherical solar still can be used for distilled water production